(untitled) (Homoeopathy for All, 2024)
Psychosomatic disorders are Concerned with bodily symptoms caused by emotional disturbances i.e., relationships among social, psychological, behavioral factors on bodily processes and quality of life. So complete cure from this can be only achieved when the cause for the generation of the mental stress is identified. This review highlights the important aspects of the psychosomatic diseases and the concept of homoeopathic philosophy. According to Homoeopathic philosophy, when an individual becomes normalized by the homoeopathic cure, the deeper side of his being, the will and the understanding or the rational mind are balanced. With the change in the mental and moral sphere, the physical health improves with a high degree of resistance to maladies of all kinds. Such is the transition from constitutional weakness and suffering to homoeopathic health and comfort.